Teachers’ Implicit Theories of Professional Abilities in the Domain of School Improvement - Rechsteiner, Beat; Compagnoni, Miriam; Wullschleger, Andrea; Maag Merki, Katharina (Frontiers in Education, 2021)
Numerous studies show positive effects of students’ malleable implicit theories of their abilities on their self-regulated learning and learning achievements (Yeager and Dweck, 2012; Burnette et al., 2013), especially when domain-specific implicit theories are assessed (Costa and Faria, 2018). Thinking of school improvement as a collective learning process for the teaching staff, it is reasonable to assume that this relationship also exists on the teacher level. Hence, this study aims to provide answers to the following overarching question: What role do teachers’ implicit theories of professional abilities play for school improvement? In a first step, a measurement instrument was developed to assess teachers’ implicit theories of professional abilities in the domain of school improvement. In a second step, we explored the link between these implicit theories and collective teacher learning in the area of further developing the school’s educational practices. In a sample of N = 1,483 Swiss primary school teachers at N = 59 schools, we analyzed how teachers’ malleable (vs. fixed) implicit theories of professional abilities are related to collective metacognitive and emotional-motivational regulation activities and to the perception that the school is on the right track to improvement. Results show that teachers’ implicit theories of professional abilities can be assessed reliably. Structural equation modeling analyses revealed that the more teachers view professional abilities as malleable and developable, the more positive their perceptions of the schools’ improvement were. This relation was mediated by collective emotional-motivational regulation activities. However, no significant effect of a malleable implicit theory on collective metacognitive regulation was found. It can be concluded that teachers have varying beliefs about the malleability of teachers’ professional abilities that are linked to their collective regulation. It therefore acknowledges the domain-specific effects of teachers’ implicit theories in the area of school improvement.